Assessing the maturity of alternative construction materials and their potential impact on embodied carbon for single-family homes in the American Midwest - Ranganath, Sindhuja; McCord, Stephen; Sick, Volker (Frontiers in Built Environment, 2024)
This study presents a whole building life cycle assessment for a 265 m 2 end-terrace home built in Michigan, US. The study scrutinized the embodied carbon footprint of conventional construction materials, focusing on high-impact materials like concrete, steel, gypsum, paint, and insulation. Stages from raw material extraction to transportation and processing of the raw materials into finished products and transportation of finished product to the site are considered. The baseline materials contributed to approximately 28,450 kg CO2e, equivalent to 107.35 kg CO2e/m². A notable reduction in the embodied carbon footprint, ranging from 19% to 39%, was observed by substituting with 'like-for-like' alternatives. However, the study highlighted challenges in shifting to lowembodied carbon materials, primarily due to limited market readiness and scalability of some ecofriendly options. The study also assessed the feasibility of these alternatives using the US Department of Energy's "Technology Readiness Level" framework, examining their current production capacity, estimating potential future demand, and identifying key development areas to meet net-zero carbon goals effectively. This comprehensive approach underscores the complexity of transitioning to low embodied-carbon building practices while balancing feasibility and environmental impact.